The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1183/23120541.00117-2019
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing of transplant-stage idiopathic pulmonary fibrosis lung reveals unique pathway regulation

Abstract: Idiopathic pulmonary fibrosis (IPF), the scarring of lung parenchyma resulting in the loss of lung function, remains a fatal disease with a significant unmet medical need. Patients with severe IPF often develop acute exacerbations resulting in the rapid deterioration of lung function, requiring transplantation. Understanding the pathophysiological mechanisms contributing to IPF is key to develop novel therapeutic approaches for end-stage disease.We report here RNA-sequencing analyses of lung tissues from a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 43 publications
(42 reference statements)
5
45
0
Order By: Relevance
“…Thus, changes in the expression levels of these candidate genes by p38 activity may be involved in promoting fibrosis through molecular interactions between epithelial and immune cells in the IPF lung. This hypothesis is supported by two previous reports showing an association of lymphocytes and epithelial cells with progressive fibrosis in transcriptome analysis of IPF lungs [60,61]. Therefore, the interplay between these genes and the p38 MAPK pathway may be key to understanding the immunological mechanisms underlying IPF progression.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, changes in the expression levels of these candidate genes by p38 activity may be involved in promoting fibrosis through molecular interactions between epithelial and immune cells in the IPF lung. This hypothesis is supported by two previous reports showing an association of lymphocytes and epithelial cells with progressive fibrosis in transcriptome analysis of IPF lungs [60,61]. Therefore, the interplay between these genes and the p38 MAPK pathway may be key to understanding the immunological mechanisms underlying IPF progression.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, MEOX1 expression was significantly up-regulated in human diseases that prominently feature fibrosis, such as heart tissue from patients with cardiomyopathy and lung tissue from patients with idiopathic pulmonary fibrosis (Fig. 4H,I) 30 .…”
Section: Introductionmentioning
confidence: 99%
“…2H and Extended data Fig. 4A), a homeodomain-containing TF that is expressed in paraxial mesoderm and is required for sclerotome development 29,30 . Meox1 was particularly interesting because it was minimally expressed in the healthy mouse heart but highly upregulated in MyoFBs following TAC ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that ECs were experimentally generated using a specific cell culture method and that their in vivo relevance is yet to be determined. Overlapping findings with the GSE134692 dataset based on primary tissue specimens from lung transplant recipients and donors [16] suggest, however, that our model may be able to capture the principal signatures of the IPFaffected lung including upregulation of CXCL8, LIF, and PTGS2. CXLC8 (encoding interleukin 8) is an inflammatory mediator attracting neutrophils and contributing to pathogen clearance, but may also confer secondary fibrotic tissue damage [18,19].…”
Section: Discussionmentioning
confidence: 95%
“…As shown in Supplementary Figure 1A, four out of five key genes (CXCL8, ICAM1, LIF, PTGS2) could be validated as overexpressed in IPF, with the remaining gene (IL7R) showing enrichment in IPF samples as well without reaching statistical significance. Moreover, comparing these key genes to the publically available GSE134692 dataset [16], we found that three of the genes (CXCL8, LIF, PTGS2) showed the same direction of regulation among IPF and non-IPF samples, whereas ICAM1 and IL7R were differentially regulated between the datasets ( Supplementary Figure 1B). This suggested both similarities and characteristic differences between the datasets, thus corroborating our findings but also highlighting the distinct nature of our ex vivo model in comparison to primary explanted tissue.…”
Section: Principal Signatures Of Ecs From An Ipf Sourcementioning
confidence: 97%